Systematic Literature Review (SLR): ESG and Firm Value - Siti Nurlatifah; Triwidyastuti; Nurmala Ahmar (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2025)
This systematic literature review aims to comprehensively summarize, analyze, and synthesize empirical evidence regarding the relationship between Environmental, Social, and Governance (ESG) performance and corporate value, while identifying causal mechanisms and contextual factors that moderate their impact. Using the PRISMA protocol-based Systematic Literature Review (SLR) methodology, an extensive literature search was conducted on major academic databases for articles published between 2016-2025, with a systematic process of selection, data extraction, and quality assessment. We anticipate the findings will demonstrate the consistency of the positive relationship between ESG and corporate values, while acknowledging inconsistencies caused by differences in methodology or market context, as well as clarifying key mechanisms and moderation factors (e.g., industry characteristics, governance). The results of this review are expected to provide practical insights for managers in integrating ESG authentically, investors in developing advanced investment models, and regulators (OJK, IDX) in standardizing ESG reporting to improve market transparency. The originality and value of this research lies in a comprehensive synthesis of the diverse research landscape, clarifying findings, and formulating a directed future research agenda, particularly highlighting the need for studies in emerging markets such as Indonesia.